A proposed biologically-inspired model to analyze signal sound - Hamzah, Hammuzamer Irwan; Abdullah, Azween (2009)
Sound is one of the media that brings information to human.However this information also distracted by noises that surround us.How human brain recognizes to the required sound is very much impressive.Vice versa, the human brain can learn to the new sound.Thus, we can just concentrate to the sound that we want to listen only.For instance, when two human communicate each other, to be precise in a loud area such as at the market, both are paying attention merely to the conversation of what they are talking.Here, in this situation, human without notice can filter the unintended noise and only recognize to the particular sound we wanted to listen only.Hence, this research studies the human ear and human brain as a new idea to analyze sound.The human ear to be exact; the eardrum detects the signal sound and the cochlea filters the signal frequency. Subsequently, the brain is capable to identify on the required sound by recognizing and learning the signal sound.Therefore, with the analysis of the biologically-inspired entities, this research investigates the capability requirements to develop the biologically-inspired signal sound analyzer (BISSA) as a new idea for information gathering.